Preparation method of heterostructure medical bone implant based on additive manufacturing
The preparation of heterostructured bone implants of titanium alloy-iron-zinc through additive manufacturing technology has solved the problem of unsatisfactory degradation rate and biocompatibility in the biodegradation process of existing titanium alloy bone implants, and achieved the combination of mechanical properties and biological properties, improving the degradation rate and biocompatibility.
Patent Information
- Application Number
- CN202510244845.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-04
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2045-03-04
AI Technical Summary
The existing titanium alloy bone implants have problems with unsatisfactory degradation rates and biocompatibility during the biodegradation process, which is difficult to meet the mechanical and biological performance requirements of bone implants.
Using additive manufacturing technology, a titanium alloy bracket is prepared by selective laser melting technology, and an iron layer is added through electroplating method, and then the molten zinc-based metal is cast onto the titanium alloy-iron bracket to form a heterostructure of titanium alloy-iron-zinc.
The combination of the mechanical properties of the titanium alloy skeleton and the biological properties of zinc-based metals is achieved, and the appropriate degradation rate is adjusted through the galvanic corrosion effect, which improves the degradation rate of zinc, and improves biocompatibility and antibacterial properties.
Smart Images

Figure CN119703133A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for preparing a medical bone implant with a heterogeneous structure based on additive manufacturing, in particular to a method for preparing a titanium alloy-iron-zinc heterogeneous structure medical bone implant which can meet the mechanical property requirements of human bone implants, has a good degradation rate and excellent biological properties, and can reasonably regulate bone repair. Background Art
[0002] With the development of the aging population, the market demand for bone implants is expanding. Titanium alloys are considered to be good alternative candidate materials for bone implants because of their elastic modulus close to that of bones and good wear resistance. With the development of additive manufacturing technology in recent years, people have seen the possibility of using titanium alloys to prepare various interconnected porous structures, and titanium alloys have become a popular material in the field of bone implant processing and preparation. However, the biological inertness of titanium alloys has become a problem that has plagued researchers for many years.
[0003] Degradable metals refer to metal materials that can be biodegraded and absorbed by the human body. After being prepared into bone implants, as the metal gradually degrades, it is eventually replaced by new bone tissue and has good biocompatibility. The most representative of these are magnesium, zinc, iron and their alloys. Among them, iron-based degradable metal materials have excellent comprehensive mechanical properties, but the degradation rate is too low, and the corrosion products are difficult to remove from the bone implant site; magnesium-based degradable metal degradation products will be metabolized out of the body, but its faster degradation rate will cause the structure to disintegrate prematurely, and its degradation and discharge of hydrogen will affect the cell attachment of adjacent tissues, leading to cysts and embolisms; zinc-based degradable metals do not produce bubbles during the degradation process, can promote the generation of new bone cells and have certain antibacterial ability, but its hardness and mechanical strength are low, which cannot meet the mechanical requirements of bone implants, and the degradation rate is slightly slow.
[0004] Therefore, absorbing the advantages of various materials and improving the biological properties as much as possible while meeting the mechanical strength requirements of bone implant preparation has become an important trend in current research. At present, some people have studied the combination of titanium alloy and magnesium alloy to prepare heterogeneous structure bone implants, combining the mechanical properties of titanium alloy and the biological properties of magnesium alloy. However, as mentioned above, the negative effects of magnesium-based metals in the degradation process are a problem that must be faced and urgently needs to be solved. The biological properties of zinc are much better than those of magnesium alloys. Replacing magnesium with zinc can not only avoid the production of hydrogen, but also further regulate biological properties such as antibacterial properties. However, the slow degradation rate of zinc is also a problem that currently troubles scientific researchers.
[0005] The preparation of titanium alloy-iron-zinc heterostructure can fully exert the biological properties of zinc-based metals while maintaining the mechanical strength of the titanium alloy skeleton, and rationally utilize the galvanic corrosion effect to adjust the appropriate degradation rate. During the zinc degradation process, osteoclasts continuously generate new bone tissue, eventually forming a titanium alloy-bone heterostructure, which greatly promotes bone repair.
[0006] Therefore, it is necessary to select a suitable process to prepare titanium alloy and zinc-based alloy into heterogeneous structure bone implants. Summary of the invention
[0007] 1. Technical issues to be resolved In order to solve the problem of difficulty in preparing heterogeneous metal structure bone implants, the present invention provides a method for preparing heterogeneous structure medical bone implants based on additive manufacturing.
[0008] (II) Technical solution In order to achieve the above-mentioned purpose, the main technical scheme adopted by the present invention includes: a method for preparing a heterogeneous structure medical bone implant based on additive manufacturing, comprising the following steps: Step 1: Using the selective laser melting technology, TC4 titanium alloy powder is prepared into a titanium alloy stent with interconnected pores according to a suitable printing strategy; Step 2: placing the titanium alloy stent in a chemical polishing solution for polishing; Step 3: Use the chemically polished titanium alloy bracket as the cathode and the pure iron sheet as the anode, and immerse both into the electroplating solution for electroplating; Step 4: Pour the molten zinc-based metal into a square crucible with a titanium alloy-iron support, place a weight block on top, and cut after cooling.
[0009] Preferably, the titanium alloy stent in step one is a rhombic dodecahedron stent.
[0010] Preferably, the design method of the rhombus dodecahedron support is: first, according to the arc angle r, the cell side length a, and the concave side length b of the star-shaped honeycomb, a star-shaped honeycomb two-dimensional structure is drawn; then, a curved beam is arranged outside each concave side of the star-shaped honeycomb to obtain a curved beam two-dimensional structure, and the law curve of the curved beam is , rad is the unit of radians, x is the horizontal coordinate of the point on the curved beam, y is the vertical coordinate of the point on the curved beam, and the four curved beams are connected end to end through a rectangular block with a side length of h; the star-shaped honeycomb and the curved beam are thickened inwardly, with thicknesses of 0.75h and 0.25h respectively, and then the convex vertex of the star-shaped honeycomb is connected to the rectangle, and the concave vertex of the star-shaped honeycomb is connected to the top of the curved beam through a rectangle with a width of h, thereby combining the star-shaped honeycomb two-dimensional structure and the curved beam two-dimensional structure to generate a two-dimensional modified star-shaped negative Poisson's ratio structure; the two-dimensional modified star-shaped negative Poisson's ratio structure is stretched along the X-axis, and the stretching length is h; the center of the stretched two-dimensional modified star-shaped negative Poisson's ratio structure is restricted to the origin, and replicated along the XY plane and the ZX plane respectively to obtain a unit-cell modified star-shaped negative Poisson's ratio structure; finally, the unit-cell modified star-shaped negative Poisson's ratio structure is arrayed once along the X, Y, and Z axes in turn to obtain 2 2 2 Modified star-shaped negative Poisson's ratio structure array.
[0011] Preferably, the chemical polishing solution in step 2 comprises nitric acid, hydrofluoric acid and deionized water, the volume ratio of nitric acid, hydrofluoric acid and deionized water is (3-8): (1-2): (5-10), the concentration of nitric acid is 1-8 mol / L, and the concentration of hydrofluoric acid is 1-22.5 mol / L.
[0012] Preferably, the polishing time in step 2 is 1 min to 3 min.
[0013] Preferably, the electroplating solution in step three is prepared from ferrous chloride particles and deionized water, with a concentration ratio of 200-400 g / L and a pH value of 1.5.
[0014] Preferably, the electroplating conditions in step three are: the electroplating solution is placed in a 60° C. water bath, the current is 100-500 mA, and the duration is 10-50 min.
[0015] Preferably, the molten zinc-based metal is obtained by placing the zinc-based metal in a cylindrical crucible and simultaneously heating the crucible to 500-800° C. in a sintering device.
[0016] (III) Beneficial effects The present invention can evenly remove the step effect and adhered powder caused by processing inside and outside the titanium alloy bracket, ensure the bonding effect of the electroplated iron layer, and ensure the fluidity of the zinc-based metal during subsequent casting. The preparation of the iron layer can avoid the element diffusion caused by the good mutual solubility of the zinc-based metal and the titanium element, and ensure the good forming of the titanium alloy-iron-zinc heterostructure medical bone implant. At the same time, the titanium alloy-iron-zinc forms a three-electrode galvanic couple, with the titanium alloy as the cathode and the zinc as the anode. The galvanic corrosion rate generated by the three-electrode galvanic couple is significantly improved compared to the two-electrode galvanic couple of the titanium alloy-zinc and pure zinc, which can effectively improve the problem of low zinc degradation rate; After the formed titanium alloy-iron-zinc heterostructure medical bone implant is implanted into the human body, the zinc-based metal gradually degrades over time, and new bone forms on the surface. The good biocompatibility of the zinc-based metal ensures the development and growth of cells and avoids the growth of bacteria. The addition of the iron layer allows the titanium alloy-iron-zinc to form a three-electrode couple, which greatly promotes the degradation of zinc acting as the anode. The appropriate degradation rate ensures the healing of new bone tissue. At the same time, the titanium alloy skeleton provides good mechanical properties to avoid failure of the bone implant. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 is a preparation flow chart of the present invention; Figure 2 It is a schematic diagram of the forming principle of the electroplated iron layer; Figure 3 This is a schematic diagram of casting a molten zinc-based metal on a rhombic dodecahedron bracket in Example 1; Figure 4 The flowchart of the modified star-shaped negative Poisson's ratio structure array design in the present invention; Figure 5 Schematic diagram of the preparation of titanium alloy-iron-zinc heterostructure; (a) is a schematic diagram of a titanium alloy-iron bracket, and (b) is a schematic diagram of a titanium alloy-iron-zinc heterostructure; Figure 6 Schematic diagram of accelerated degradation of titanium alloy-iron-zinc three-couple corrosion; Figure 7 It is a comparison chart of the degradation rates of pure zinc, titanium alloy-zinc heterostructure, and titanium alloy-iron-zinc heterostructure; Figure 8 This is a comparison chart of the antibacterial experiment test results; Fig. 9 The figure shows the mechanical properties comparison of titanium alloy stent, titanium alloy-zinc heterostructure, and titanium alloy-iron-zinc heterostructure: (a) is the stress-strain curve, and (b) is the elastic modulus analysis comparison bar graph; In the figure, 1: titanium alloy bracket; 2: pure iron sheet; 3: electroplating solution; 4: water bath; 5: square crucible; 6: titanium alloy-iron bracket; 7: zinc-based metal in molten state; 8: cylindrical crucible; 9: weight block. DETAILED DESCRIPTION
[0018] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below through specific implementation modes in conjunction with the accompanying drawings.
[0019] Embodiment 1 of the present invention: A method for preparing a heterogeneous structure medical bone implant based on additive manufacturing, comprising the following steps: Step 1: Using the selective laser melting technology, according to a suitable printing strategy, TC4 titanium alloy powder is prepared into a titanium alloy bracket 1 with interconnected pores. Here, the titanium alloy bracket 1 is a rhombic dodecahedron bracket. The design method of the rhombic dodecahedron bracket is as follows: first, according to the arc angle r, the cell side length a, and the concave side length b of the star honeycomb, a star honeycomb two-dimensional structure is drawn, such as Figure 4 As shown in (a); then a curved beam is set outside the concave edge of each star-shaped honeycomb to obtain a curved beam two-dimensional structure. The law curve of the curved beam is , rad is the unit of radians, x is the horizontal coordinate of the point on the curved beam, y is the vertical coordinate of the point on the curved beam, and the four curved beams are connected end to end through a rectangular block with a side length of h, such as Figure 4 As shown in (b); the star-shaped honeycomb and the curved beam are thickened inwardly, with thicknesses of 0.75h and 0.25h respectively, and then the convex vertices of the star-shaped honeycomb are connected to the rectangle, and the concave vertices of the star-shaped honeycomb are connected to the top of the curved beam through a rectangle with a width of h, thereby combining the star-shaped honeycomb two-dimensional structure and the curved beam two-dimensional structure to generate a two-dimensional modified star-shaped negative Poisson's ratio structure, as shown in Figure 4 As shown in (c); the two-dimensional modified star-shaped negative Poisson's ratio structure is stretched along the X-axis, and the stretching length is h, as shown in Figure 4 As shown in (d); the center of the stretched two-dimensional modified star-shaped negative Poisson's ratio structure is restricted to the origin, and replicated along the XY plane and ZX plane respectively to obtain a unit cell modified star-shaped negative Poisson's ratio structure, as shown in Figure 4 Finally, the unit cell modified star-shaped negative Poisson's ratio structure is arrayed once along the X, Y, and Z axes to obtain 2 2 2 Modified star-shaped negative Poisson's ratio structure array, such as Figure 4 As shown in (f); Step 2: Prepare a chemical polishing solution with 2 mol / L nitric acid, 22.5 mol / L hydrofluoric acid and deionized water, wherein the volume ratio of nitric acid, hydrofluoric acid and deionized water is 4:1:5; place the titanium alloy stent 1 in the chemical polishing solution, polish for 2 minutes, take it out, wash it and dry it; Step 3: prepare an electroplating solution 3 with ferrous chloride particles and deionized water, the concentration ratio of which is 300g / L and the pH value is 1.5; use the titanium alloy bracket 1 as the cathode and the pure iron sheet 2 as the anode, immerse both in the electroplating solution 3, place the electroplating solution 3 in a 60°C water bath 4, the current is 200mA, and the duration is 20min; take out the obtained titanium alloy-iron bracket 6 after electroplating, clean the surface debris, place it in alcohol for ultrasonic cleaning and dry; Step 4: Place the zinc-based metal in a cylindrical crucible 8 and simultaneously heat it to 700°C in a sintering device to ensure the melting of the zinc-based metal; cast the molten zinc-based metal 7 into a square crucible 5 with a titanium alloy-iron bracket 6, and press it on top with a weight 9; after cooling to below the melting point of the zinc-based metal, quickly cool it with water, take it out and cut it to obtain a titanium alloy-iron-zinc heterostructure.
[0020] The printing parameters used in the "appropriate printing strategy" in step 1 can be laser power 125w, scanning speed 600mm / s, scanning spacing 80μm, and scanning layer thickness 30μm. This printing parameter has been proven to have good molding accuracy in previous studies.
[0021] Embodiment 2 of the present invention: Only step 1, step 2 and step 4 of embodiment 1 are included, namely: obtaining a titanium alloy-zinc heterostructure.
[0022] Embodiment 3 of the present invention: Only step 1 and step 2 of embodiment 1 are included, namely: polished TC4 titanium alloy powder is obtained to prepare a rhombic dodecahedron bracket with interconnected pores.
[0023] Embodiment 4 of the present invention: Solid block of polished TC4 titanium.
[0024] Comparative Example 1: Pure zinc block.
[0025] Experimental Example 1 Degradation rate determination: The degradation rates of Examples 1 and 2 and Comparative Example 1 were measured. The degradation rates of each group are shown in Table 2.
[0026] Detection method: Prepare the simulated body fluid according to Table 1, hang the sample in the center of the beaker with a wire, and conduct an immersion test for 28 days. After the immersion is completed, take out the sample, measure the mass change, and calculate the degradation rate. Test 5 parallel samples for each group of samples.
[0027] Table 1. Ratio of simulated body fluids Element Concentration (g / L) NaCl 8.00 KCl 0.40 <![CDATA[NaHCO3]]> 0.35 <![CDATA[CaCl2]]> 0.14 <![CDATA[KH2PO4]]> 0.10 <![CDATA[MgSO4·H2O]]> 0.20 <![CDATA[C6H 12 O6]]> 1.00 <![CDATA[NaHPO4]]> 0.06 Sample size: 10mm*10mm*10mm Test steps: ① Conduct mass test and surface area calculation before immersion; ② Perform simulated body fluid preparation; ③ Perform immersion test; ④ Perform mass calculation; ⑤ Perform degradation rate calculation.
[0028] Table 2 Degradation rate determination results Example 1 Example 2 Comparative Example 1 Element Titanium Alloy-Iron-Zinc Titanium Alloy-Zinc Zinc Degradation rate (Mm / year) 0.4236±0.0490 0.2234±0.0098 0.0279±0.0029 Experimental conclusion: The heterogeneous structure of titanium alloy-iron-zinc can greatly increase the degradation rate of zinc, providing ideas for rationally regulating the degradation rate of zinc in the human body.
[0029] Experimental Example 2 In vitro antibacterial experiment: Examples 1, 2, 4 and comparative example 1 were used to determine the in vitro antibacterial rate of common infectious bacteria (Escherichia coli and Staphylococcus aureus). The in vitro antibacterial rate of each group is shown in Table 3. According to relevant standards such as "JIS Z2801-2000 "Antibacterial processed products-Antibacterial test method and antibacterial effect", GB / T2591-2003 "Antibacterial plastic antibacterial performance test method and antibacterial effect"".
[0030] The calculation formula of the antibacterial rate is: ; Where Cs is the inhibition rate, A is the number of cells in the test group, B is the number of cells in the blank group, and C is the number of cells in the control group.
[0031] Detection method: Mouse embryonic osteoblast precursor cells MC3T3-E1 were used for in vitro biocompatibility testing. Mouse embryonic osteoblast precursor cells MC3T3-E1 were cultured in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% fetal bovine serum (FBS), 100 μg / mL streptomycin and 100 U / mL penicillin in 5% CO 2 The cells were cultured at 37°C in a humidified atmosphere. The medium was changed every other day and the third generation cells were used for the experiments. Cell viability and alkaline phosphatase (ALP) activity were assessed by extraction assay. Sample extracts were prepared according to the guidelines of ISO10993-5. Briefly, samples were immersed in the medium for 24 h at 37°C (sample area / medium volume = 1.25 cm 2 / mL). Cell viability was assessed using the CCK-8 method. Mouse embryonic osteoblast precursor cells MC3T3-E1 (2×10^ 3 Cells / well) were seeded in 96-well plates and incubated at 37°C, 5% CO 2The cells were incubated for 24 hours at 4 °C. Subsequently, the growth medium was replaced with the sample extract (100 μL) for further culture. DMEM was used as a negative control. CCK-8 solution (10 μL) was added to each well on days 1, 3, and 5, followed by incubation for 2 hours. The optical density (OD) value at a wavelength of 450 nm was measured using a microplate spectrophotometer (Biotek, USA).
[0032] Test steps: ① Cultivate bacteria; ② Inoculate bacteria into the sample immersion solution; ③ Calculate the number of surviving cells; ④ Calculate the inhibition rate.
[0033] Table 3 Antibacterial rate results Example 1 Example 2 Example 4 Comparative Example 1 Element Titanium Alloy-Iron-Zinc Titanium Alloy-Zinc Titanium Alloy Zinc Staphylococcus aureus inhibition rate (%) 99.69±1.36 97.35±1.02 18.89±2.70 90.45±2.10 Escherichia coli inhibition rate (%) 98.34±0.94 91.26±1.95 17.06±3.10 89.04±1.40 Experimental conclusion: The heterogeneous structure of titanium alloy-iron-zinc has obvious antibacterial effect compared with titanium alloy materials.
[0034] Experimental Example 3 Mechanical Properties Determination: The elastic modulus and strain of Examples 1-3 were measured. The elastic modulus measurement results of each group are shown in Tables 4 and Fig. 9 (b), strain measurement results see Fig. 9 (a).
[0035] Elastic modulus determination and testing method: Use a universal testing machine to perform compression testing on the sample, convert the compression data into a stress-strain curve, and then measure the slope of its linear elastic stage. The result is the elastic modulus.
[0036] Sample size: 10mm*10mm*10mm Test steps: ① compression test; ② data processing; ③ elastic modulus measurement in linear elastic stage.
[0037] Table 4 Elastic modulus measurement results Example 1 Example 2 Example 3 Element Titanium Alloy-Iron-Zinc Titanium Alloy-Zinc Titanium Alloy Elastic modulus (GPa) 2.23±0.06 2.42±0.05 0.94±0.05 Experimental conclusion: The mechanical properties of the titanium alloy-iron-zinc heterostructure are significantly improved compared to titanium alloy stents, and are still within the mechanical properties requirements of natural human bones (1~35GPa).
Claims
1. A method for preparing a heterogeneous structure medical bone implant based on additive manufacturing, characterized in that: The following steps are involved: Step 1: Using the selective laser melting technology, TC4 titanium alloy powder is prepared into a titanium alloy stent with interconnected pores according to a suitable printing strategy (1); Step 2: placing the titanium alloy stent (1) in a chemical polishing solution for polishing; Step 3: The chemically polished titanium alloy bracket (1) is used as a cathode, and the pure iron sheet (2) is used as an anode, and both are immersed in an electroplating solution (3) for electroplating; Step 4: Cast the molten zinc-based metal (7) into a square crucible (5) with a titanium alloy-iron support (6), and place a weight block (9) on top, and cut after cooling.
2. The method for preparing a heterogeneous structure medical bone implant based on additive manufacturing according to claim 1, characterized in that: The titanium alloy stent (1) in step 1 is a rhombic dodecahedron stent.
3. The method for preparing a heterogeneous structure medical bone implant based on additive manufacturing according to claim 2, characterized in that: The design method of the rhombus dodecahedron bracket is as follows: first, a star-shaped honeycomb two-dimensional structure is drawn according to the arc angle r, the cell side length a, and the concave side length b of the star-shaped honeycomb; then, a curved beam is set outside each concave side of the star-shaped honeycomb to obtain a curved beam two-dimensional structure. The law curve of the curved beam is , rad is the unit of radians, x is the horizontal coordinate of the point on the curved beam, y is the vertical coordinate of the point on the curved beam, and the four curved beams are connected end to end through a rectangular block with a side length of h; the star-shaped honeycomb and the curved beam are thickened inwardly, with thicknesses of 0.75h and 0.25h respectively, and then the convex vertex of the star-shaped honeycomb is connected to the rectangle, and the concave vertex of the star-shaped honeycomb is connected to the top of the curved beam through a rectangle with a width of h, thereby combining the star-shaped honeycomb two-dimensional structure and the curved beam two-dimensional structure to generate a two-dimensional modified star-shaped negative Poisson's ratio structure; the two-dimensional modified star-shaped negative Poisson's ratio structure is stretched along the X-axis, and the stretching length is h; the center of the stretched two-dimensional modified star-shaped negative Poisson's ratio structure is restricted to the origin, and replicated along the XY plane and the ZX plane respectively to obtain a unit-cell modified star-shaped negative Poisson's ratio structure; finally, the unit-cell modified star-shaped negative Poisson's ratio structure is arrayed once along the X, Y, and Z axes in turn to obtain 2 2 2 Modified star-shaped negative Poisson's ratio structure array.
4. The method for preparing a heterogeneous structure medical bone implant based on additive manufacturing according to claim 1, characterized in that: The chemical polishing solution in step 2 includes nitric acid, hydrofluoric acid and deionized water, and the volume ratio of nitric acid, hydrofluoric acid and deionized water is (3-8): (1-2): (5-10), the concentration of nitric acid is 1-8 mol / L, and the concentration of hydrofluoric acid is 1-22.5 mol / L.
5. The method for preparing a heterogeneous structure medical bone implant based on additive manufacturing according to claim 1, characterized in that: The polishing time in step 2 is 1 min to 3 min.
6. The method for preparing a heterogeneous structure medical bone implant based on additive manufacturing according to claim 1, characterized in that: The electroplating solution (3) in step 3 is prepared from ferrous chloride particles and deionized water, with a concentration ratio of 200-400 g / L and a pH value of 1.
5.
7. The method for preparing a heterogeneous structure medical bone implant based on additive manufacturing according to claim 6, characterized in that: The electroplating conditions in step three are as follows: the electroplating solution (3) is placed in a 60° C. water bath (4), the current is 100-500 mA, and the duration is 10-50 minutes.
8. The method for preparing a heterogeneous structure medical bone implant based on additive manufacturing according to claim 1, characterized in that: The molten zinc-based metal (7) is obtained by placing the zinc-based metal in a cylindrical crucible (8) and simultaneously heating the mixture to 500-800° C. in a sintering device.
Citation Information
Patent Citations
Novel titanium alloy for bone implantation and preparation method thereof
CN108285990A
Preparation method of biomedical degradable metal framework reinforced Zn-based composite material with large-area galvanic corrosion structure
CN114042898A
Hot stamping assembly and manufacturing method thereof
CN117858976A
Titanium-magnesium bimetallic composite material as well as preparation method and application thereof
CN118699359A
Method for preparing nano structure on surface of Ti6Al4V implant structure through additive manufacturing
CN118699409A
Cited By
Multifunctional intravascular stent with negative Poisson's ratio structure and preparation method of multifunctional intravascular stent
CN121571655A